A Qualitative Investigation of Customers’ Preferences for Ayurvedic Beauty Products over Cosmetic Products - Pallathadka, Laxmi Kirana; Pallathadka, Harikumar; Devi, Mairembam Sangita (Integrated Journal for Research in Arts and Humanities, 2022)
Today, everyone is keen on showing their actual appearance as excellence. Also, they like to defend themselves from wellbeing risks by utilizing different restorative things. The explanation is that many organizations are fabricating both synthetic and ayurvedic-based restorative items. At first, natural items have a low market. Then, at that point, the acknowledgment of natural items is expanding in India and global business sectors. Moreover, this was occurred after understanding the side eﬀects of synthetic-based restorative items. In this unique circumstance, the analysts have chosen to direct the ﬁeld study identifying with customer mindfulness and inclinations towards ayurvedic restorative items in Coimbatore city. To work on the nature of the exploration, the scientists have chosen to think about the mindfulness and inclinations of customers towards ayurvedic and non-ayurvedic restorative items. The measurable devices like the chi-square test and rank examination are utilized to ﬁnd the signiﬁcant relationship between close-to-home elements of respondents and different parts of the items.